A Case Study of Code-switching in a City of East China - Xiaoping Jie (Universitas Cokroaminoto Palopo, 2017)
This study attempts to observe how natives of different age groups in a city of south-east China switch between Putonghua (Mandarin Chinese), the H language variety, and the local dialect, the L variety, the linguistic features of different CS patterns, and the function of the H variety in conversation. Topics of the participants’ conversations ranged from family to friends, neighborhood, games, movies, computers and business. Data analysis shows that the participants mainly use the local dialect and Putonghua in their daily conversation, while English and other dialects in China like Cantonese and Dongbeihua (Dialect in north-east China) are also used.